Jamuro Religious Factors: Perspective of Islamic Education Psychology - Jony Muhandis; Muhammad Nurul Yamin; Syarifan Nurjan (Universitas Muhammadiyah Yogyakarta, 2020)
Jamaah Muji Rasul Surakarta goes through the religious process of Sufi life, which is to cleanse yourself from the impurities of the heart and keep away from the low behavior in life with the intention to always worship God. This study aims to describe the factors that influence the diversity of the Muji Rosul Jamaat perspective in the psychology of Islamic education and its contribution to Islamic education. This study uses a qualitative research approach with the perspective of Islamic educational psychology that uses descriptive analysis method. The results of the study illustrate that the factors that influence religious diversity are the intensity of muji Rosul through tabligh activities, tahlilan and shalawatan able to strengthen the diversity of worshipers who are carried out routinely every Monday Pon, tarling, gebyar maulid, evening compensation, raising funds for the construction of mosques and musholla, white clothes or tend to be bright, because of the colors favored by the Prophet's Kanjeng, and colors that are simple and easy to obtain, look clean and there is no difference between worshipers, analyzing human behavior with religious knowledge and baraka.